INITIAL BREEDING MATERIAL OF VEGETABLE BEAN FOR DEVELOPMENT OF EARLY-RIPENING VARIETIES IN NORTH PART OF FOREST STEPPE OF THE UKRAINE - E. N. Grishenko; V. L. Zhemoiyda (Овощи России)
The collection of vegetable bean varieties was screened for duration of vegetative and interstage periods. The initial breeding material as a source of early-ripeness was selected.